Estructuras arquitectónicas incipientes y áreas de explotación minera prehispánica de las cuencas de los ríos Grande y Coclé del Sur, Panamá - Mojica, Alexis; Mayo, Carlos; Gracia, Guillermina Itzel De; Moreno, Enrique; Ruiz, Alberto; Mayo, Julia (Revista Española de Antropología Americana, 2007)
Archaeological researches realized up today in Gran Coclé, have always been focused, as isolated studies, on certain types of sites as for example rock shelters, shell-bearing middens sites or burials. The result is a parcial view of the historical and cultural development of this region, due that all of these studies raise specific subjects like isolated ideas (diet, lithic technology...). Our research, which parcial results of the first two years of researchs that we develop in a dossier, agglutinates all this information regarding a wide spatial context, using Geographical Information System (GIS), and considering a more diversity of sites, some of which are unpublished, like the small scale architectural features and prehispanic mines